Analysis of the use collocation aviation polytechnic’ thesis abstract - Risca Hidayanti Qurani; Noviatul Rochmah; Yudhi Arifani; Candra Hadi Asmara (Jetlal, 2023)
Collocation is also a good way to memorize new words. Words that are naturally associated in context are more effectively understood than those not associated; vocabulary is better taught in context; context alone is inadequate without deliberate connection. Context and deliberate association, particularly collocations, offer connections that allow learners to understand thoroughly the meaning of a word and to add it to their existing vocabulary. The aim of correct collocation during a conversation between a pilot and air traffic controller is to minimize the risk o misunderstandings a well-defined set of words are used in mostly the same sequence when clearances are given by the Air Traffic Controller and read back by Pilots.